Evaluation of Volume Controlled Ventilation Mode and Volume Guaranteed Pressure Controlled Ventilation Modes in Lateral Decubitus Position; Randomized Controlled Study - Erkan Cem Çelik; Kenan Gülbahar; Ela Nur Medetoğlu Köksal; Veysel Köksal (Atatürk Üniversitesi Tıp Fakültesi Cerrahi Tıp Bilimleri Dergisi, 2024)
Objectives: This study aims to examine the impact of two ventilation modes—volume-controlled ventilation (VCV) and volume-guaranteed pressure-controlled ventilation (PCV-VG)—on patient hemodynamic, lung mechanics, and alveolar gas exchange during laparoscopic surgery in the lateral decubitus position under general anaesthesia.Methods: The study included 60 patients, aged 18-65, classified as ASA I-II, who were scheduled for laparoscopic nephrectomy. Patients were randomly assigned to either the VCV or PCV-VG group. Parameters such as peak pressure (Ppeak), mean pressure (Pmean), PaO2, PaCO2, SaO2, and haematocrit (htc) were recorded at four time points: in the supine position before lateral decubitus (T1), 5 minutes after lateral decubitus (T2), at the end of surgery in lateral decubitus (T3), and in the supine position before extubation (T4). Additional data collected included patient demographics, surgery details, operation time, and the side of the operation.Results: When ventilation parameters and blood gas values at T1, T2, T3 and T4 were evaluated, significant differences were seen between the groups in Ppeak at T2 and Pmean at T3 (P.05). There was a significant difference in Ppeak, Pmean, htc, systolic blood pressure (SBP), diastolic blood pressure (DBP) and pulse parameters between the groups at different time periods (P